The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1177/026835559701200404
|View full text |Cite
|
Sign up to set email alerts
|

Angioscopic External Valvuloplasty in the Treatment of Varicose Veins

Abstract: Objective: To report on the surgical treatment of varicose veins by angioscopic valvuloplasty to preserve the long saphenous vein (LSV) and the efficacy of this method compared with conventional stripping and high ligation. Methods: A total of 306 limbs in 187 patients with reflux at the sapheno-femoral junction to below knee level were operated on using intraoperative angioscopy to diagnose valve insufficiency. Angioscopic external valvuloplasty was attempted for the subterminal valves in the LSV by three tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…There are discrepancies in the literature relating to the applicability of the technique. 12 Corcos et al13 found that the valvuloplasty technique was applicable in only 8.2% of varicose vein cases and 63.3% of early varicose veins. This may be explained by patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…There are discrepancies in the literature relating to the applicability of the technique. 12 Corcos et al13 found that the valvuloplasty technique was applicable in only 8.2% of varicose vein cases and 63.3% of early varicose veins. This may be explained by patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The patients comprised 28 males and 60 females, ranging in age from 29 to 79 years (mean 55.8 years). 14,15 The patients comprised 28 males and 60 females, ranging in age from 29 to 79 years (mean 55.8 years).…”
Section: Methodsmentioning
confidence: 99%
“…Angioscopic valvular incompetence was classified into three types and valvuloplasty was applied in valves with type I or type II: 14,15 Type I: valves with elongated and atrophic cusps. A bloodless field was obtained by manually flushing normal saline through a flush channel.…”
Section: Methodsmentioning
confidence: 99%
“…A bloodless field was obtained by manually flushing normal saline through a flush channel. Angioscopic external valvuloplasty was performed as described by Hoshino et al, 14,15 with plication of the commissure from outside the vein wall using 7-0 polypropylene (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%